Peran Influencer, Electronic Word Of Mouth (E-Wom), Live Streaming Terhadap Keputusan Pembelian Kosmetik Pada Aplikasi Shopee - Michelle Gloria Winardy; Amelia Grace Chandra; Marchello Raymond; Michella Laurent Laudy; Ayumi Angelina; Gracela Marisa Sanapang (Jurnal Online Manajemen ELPEI, 2026)
This study aims to examine the influence of influencers, Electronic Word of Mouth (E-WOM), and live streaming on purchasing decisions for cosmetic products on the Shopee app. The research method used is quantitative with purposive sampling technique involving 158 respondents from Makassar City who have previously purchased cosmetics through Shopee. Data were collected through a questionnaire and analyzed using SPSS version 26 through validity tests, reliability tests, and multiple linear regression. The results show that all three variables influencers, E-WOM, and live streaming have a positive and significant effect on purchasing decisions, both partially and simultaneously. Among the three, live streaming has the largest impact. This is because consumers feel more confident when they can see live product demonstrations, interact with sellers in real-time, and receive special promotions during the live broadcast. Meanwhile, E-WOM also plays an important role, as consumers tend to consider reviews and the experiences of other users before making a purchase. Influencers have a smaller effect compared to the other two variables, as not all consumers feel personally connected to recommendations from influencers. Overall, these three variables can explain 63.5% of the variance in purchasing decisions. Therefore, a good combination of influencers, E-WOM, and live streaming will increase consumer trust and willingness to purchase the product, ultimately boosting sales and customer loyalty.